2021
DOI: 10.3390/nu13062124
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Dietary Composition on Water Turnover Rates in Active and Sedentary Men

Abstract: Body water turnover is a marker of hydration status for measuring total fluid gains and losses over a 24-h period. It can be particularly useful in predicting (and hence, managing) fluid loss in individuals to prevent potential physical, physiological and cognitive declines associated with hypohydration. There is currently limited research investigating the interrelationship of fluid balance, dietary intake and activity level when considering body water turnover. Therefore, this study investigates whether diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
1
Order By: Relevance
“…The results of the study con rmed the differences between athletes and general population. Moreover, due to the differences in sweat output during increased energy expenditure from physical activity, studies also revealed that the differences of the contribution of dietary composition on water turnover rates in active and sedentary men [53]. Furthermore, the TBW, ICW and ECW among athletes were 47.46, 28.86 and 18.60 kg, which were all higher than the values of participants in the present study, even with the same age [45].…”
Section: Discussioncontrasting
confidence: 53%
“…The results of the study con rmed the differences between athletes and general population. Moreover, due to the differences in sweat output during increased energy expenditure from physical activity, studies also revealed that the differences of the contribution of dietary composition on water turnover rates in active and sedentary men [53]. Furthermore, the TBW, ICW and ECW among athletes were 47.46, 28.86 and 18.60 kg, which were all higher than the values of participants in the present study, even with the same age [45].…”
Section: Discussioncontrasting
confidence: 53%